Application Of Progressive Muscle Relaxation Meditation Therapy In An Aggregate Community Of Elderly With Hypertension In Sawah Lebar Urban Village, Ratu Agung Sub-District, Bengkulu City - Rahayu, Supi; Saputra , Ega Giant; Anita , Yuli; Hamzahaz , Hamzahaz; Rahmaryanti , Annisa; Nuh, Yalta Hasanuddin; Handayani, Tita Septi (Universitas Dehasen Bengkulu, 2024)
Hypertension is an invisible killer that rarely causes symptoms. Increasing public awareness is key, as is access to early detection. Rising blood pressure is a serious warning sign that important lifestyle changes are urgently needed.One of the other factors that affect hypertension is a family history, biological parents have a history of hypertension then it will be a 45% chance of being passed on to their offspring, and if only one parent has hypertension then there is a 30% chance that it will be passed on to their offspringPatient knowledge and awareness about hypertension is an important factor in achieving blood pressure control. Knowledge about hypertension is a bad lifestyle habit that contributes to the occurrence of hypertension, If a person's weight increases, then the blood volume will also increase so that the burden of the heart in pumping blood also increases.Progressive muscle relaxation techniques are deep muscle relaxation techniques that do not require imagination, perseverance, or suggestion, based on the belief that the human body responds to anxiety and thought-provoking events with muscle tension to have an effect on blood pressure.The method used in this activity is to demonstrate progressive muscle relaxation meditation therapy to the community in Sawah Lebar Village, Bengkulu City. As a result of this counseling activity, the people who suffer from hypertension in progressive muscle relaxation meditation relaxation therapy activities are very enthusiastic about participating in activities starting from the beginning until the activity is completed.